An ecology of high-altitude infancy : a biocultural perspective - Wiley, Andrea S., 1962- (Cambridge studies in medical anthropology ;, 2004)
This book considers how the unique mountain ecology and socio-cultural patterns of the Himalayan region of Ladakh contribute to a peculiar pattern of infant mortality. Highlighting the roles of ecology, culture, history, and political economy, it stresses the burdens of women's work in this region as crucial to birth outcome.